2009
DOI: 10.1111/j.1944-9720.2009.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Attitudes Toward Native and Non‐Native Language Instructors

Abstract: This study investigates students' attitudes toward native and nonnative speaking instructors of Spanish. A quantitative questionnaire was administered to 292 students enrolled in three different levels of undergraduate Spanish courses at a U.S. university. Participants were asked to rate Likert scale items related to native versus nonnative speaking instructors' knowledge and teaching ability, as well as their own potential to learn from the instructors. Results indicate that students perceive native speaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…The speech evaluators, however, tended to not be NSs of Spanish, but rather were NSs of English with varying levels of familiarity with Spanish-accented speech. So the pronunciation and accent evaluations in Arizona may have resulted in reducing the number of teachers in the classroom who shared an L1 with the students, something that has been shown to be beneficial in language learning programmes (Hertel & Sunderman, 2009;Marian et al, 2008;Park, 2012). As in Scales et al's (2006) and Isaacs' (2008) research, we found that comprehension was a high priority for students in accepting a speaker as a teacher.…”
Section: The Role Of Accent Familiaritysupporting
confidence: 50%
See 3 more Smart Citations
“…The speech evaluators, however, tended to not be NSs of Spanish, but rather were NSs of English with varying levels of familiarity with Spanish-accented speech. So the pronunciation and accent evaluations in Arizona may have resulted in reducing the number of teachers in the classroom who shared an L1 with the students, something that has been shown to be beneficial in language learning programmes (Hertel & Sunderman, 2009;Marian et al, 2008;Park, 2012). As in Scales et al's (2006) and Isaacs' (2008) research, we found that comprehension was a high priority for students in accepting a speaker as a teacher.…”
Section: The Role Of Accent Familiaritysupporting
confidence: 50%
“…Accent bias that surfaces during such assessments may lead towards the hiring of NS teachers over NNS teachers , even though the NNS teachers may have better teaching skills (as summarized by Hertel & Sunderman, 2009;Moussu, 2010). Or, as described in the literature, NS teachers may be hired first and foremost over NNS teachers (the so-called native speaker fallacy, as observed by Clark & Paran, 2007; Kahmi-Stein, 2004;Moussu, 2010;Park, 2012) because NSs are believed to be best at teaching, mainly because they are considered to have the language variety learners may want and because they are able to serve as expert cultural ambassadors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, according to Hertel and Sunderman's (2009) survey results, native English speaking teachers (NESTs) are more knowledgeable, and their teaching potential is much higher than that of NNESTs, which leads to an increase in the learning potential of students taught by NESTs. In addition, students are comfortable in their classes with NESTs, who are friendly and lenient, making the learning environment relaxing and less threatening (Alseweed, 2012).…”
Section: Native Vs Non-native General Perceptionsmentioning
confidence: 78%